Knowledge about diagnostic ionizing radiation in a population of southern Brazil - da Silva, Carina; Burkert da Silva, Carina; Cozza dos Santos, Thais; Moraes de Borba, Alana; Nunes Gomes, Bianca; Litchina Brasil, Carolina; Vitor Barboza, Daniele; da Silva Bernardi, Andreza; de Lima Wachholz, Peter; Albuquerque de Oliveira Cavalcanti, Guilherme (Pubvet, 2019)
The ionizing radiation it is very used in diagnostic medicine and applied in radiography and computerizing tomography exams. However, it is capable of cause deleterious effects in exposed organisms by means of genetic mutation, cancer, skin injuries and attached glands, ophthalmic injuries and malformation and fetal death. Therefore, through a quiz of object questions with multiple choices available in Google® Forms platform it was evaluated the knowledge of the population of Pelotas (RS) about methods of diagnostic imaging exams, the possible harmful effects from ionizing radiation exposure and it was collected data about the use of radiological protection in radiological services. Also, it was questioned about genre, scholarity and has or not training in health, looking for correlates this information with the answers. It was noticed that majority of the questioned people are not clear about diagnostic imaging exams and which ones use ionizing radiation. Most of them have knowledge about some risks of ionizing radiation in the body, however many of them reported have not been offered radiological protection equipment and verbal instruction at the moment of perform the radiological exams. The present study shows an imminent necessity of lend more information to the population respect this subject, mostly between health professionals.